Respiratory microbiome and its susceptibility to Mycobacterium tuberculosis infection - Semail, Noreafifah (2019)
Respiratory throat acts as an ecological niche for various microorganisms. These microbial communities play important roles in the maintenance of human health. Although the interest in microbial composition of microbiota in respiratory tracts has recently been increased, the possible relationship between the composition and abundance of microbiota in the ecological niche of human throat with Mycobacterium tuberculosis infection are poorly understood. This study was aimed to investigate the composition of throat microbiota in pulmonary tuberculosis patients in comparison to healthy TST (Tuberculin Skin Test) positive and TST negative subjects. The microbiota of the throat was fully characterized by 16s rRNA Metagenomics sequencing. The study revealed that altogether, there were 7 phyla and 35 genera in the throat of enrolled subjects. The main phyla were Firmicutes, Bacteriodetes, Proteobacteria and Actinobacteria. The predominant communities of genera were Streptococcus, Staphylococcus, Capnocytophaga, Rothia and Enterococcus. The microbiota composition of TB patients and asymptomatic TST positive subjects were more heterogeneous as compared to the throat microbiota of healthy TST negative subjects. Streptococcus was found to be significantly abundant in throat of healthy compared to asymptomatic TST positive subjects and TB patients. In TB patients, Bifidobacterium, Bulleidia, Butyrivibrio, Chryseobacterium and Pediococcus were among the genera present abundantly in their throats compared to TST negative. At genus level, Lactobacillus salivarius was significantly higher in the throat of TB patients compared to TST positive individuals. Streptococcus sobrinus and Bulleidia moorei were also significantly higher in TB patients when compared with those in the throats of TST negative individuals. Alpha diversity and beta diversity analysis were also performed in this study. No significant difference was observed between the three groups in alpha indices indicating the equally diverse microbiota in terms of richness and evenness of the species. In beta diversity analysis, the unweighted unifrac of TB patients and TST negative groups were statistically higher compared to TST positive group, indicating the higher presence of particular cluster or species in their throats. Weighted unifrac of TST positive was statistically higher than that of TB patients and TST negative groups which indicates more distantly related organisms inhabiting the communities. This investigation was consistent with earlier studies and our findings indicate that throat microbiota may play a role in the susceptibility or resistance to Mycobacterium tuberculosis infection. The relevance of these microbiota may need to be taken into consideration to improve methods of control of TB disease in the future.